2021
DOI: 10.1002/smll.202007090
|View full text |Cite
|
Sign up to set email alerts
|

A Photoresponsive Nanozyme for Synergistic Catalytic Therapy and Dual Phototherapy

Abstract: Dual phototherapy, including photodynamic therapy (PDT) and photothermal therapy (PTT), has shown a great prospect in cancer treatment. However, its therapeutic effect is restricted by the depth of light penetration in tissue and tumor hypoxia environment. Herein, inspired by the specific response of nanozymes to the tumor microenvironment (TME), a simple and versatile nanozyme‐mediated synergistic dual phototherapy nanoplatform (denoted as FePc/HNCSs) is constructed using hollow nitrogen‐doped carbon nanosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 36 publications
0
57
0
Order By: Relevance
“…The photothermal effect and light-induced electron transfer have been demonstrated to be involved with the photoenhanced enzyme-like activity of nanozymes [271][272][273]. With AuNPs and α-FeOOH microcrystals grown on porous carbons, Zhang et al obtained Au/α-FeOOH-FPC catalysts with visible-light-driven enzymatic property [274].…”
Section: External Triggersmentioning
confidence: 99%
See 1 more Smart Citation
“…The photothermal effect and light-induced electron transfer have been demonstrated to be involved with the photoenhanced enzyme-like activity of nanozymes [271][272][273]. With AuNPs and α-FeOOH microcrystals grown on porous carbons, Zhang et al obtained Au/α-FeOOH-FPC catalysts with visible-light-driven enzymatic property [274].…”
Section: External Triggersmentioning
confidence: 99%
“…Fluorescence spectra and X-ray photoelectron spectroscopy (XPS) data revealed that the key of S 2– -mediated activity switching mechanism lied in the structure change of protein molecule and ratio change of Pt 2+ /Pt 0 with the introduction of sulfide ions. Light The photothermal effect and light-induced electron transfer have been demonstrated to be involved with the photo-enhanced enzyme-like activity of nanozymes [ 271 273 ]. With AuNPs and α-FeOOH microcrystals grown on porous carbons, Zhang et al obtained Au/α-FeOOH–FPC catalysts with visible-light-driven enzymatic property [ 274 ].…”
Section: Properties Of Metal- and Metal Oxide-based Nanozymesmentioning
confidence: 99%
“…As a result, successful inhibition of pancreatic cell growth was achieved via photo-enhanced enzyme catalytic therapy. Yang et al designed a hollow nitrogen-doped carbon nanospheres (HNCSs) and iron phthalocyanine (FePc) for synergistic catalytic and dual phototherapy [65]. FePc/HNCSs simultaneously exhibit POD-and CAT-like activities and facilitates to convert endogenous H2O2 into ROS and O2 for tumor catalytic therapy as well as enhance O2-dependent PDT.…”
Section: Peroxidase Mimetic Nanozymes In Oxygen-dependent Cancer Photodynamic Therapymentioning
confidence: 99%
“…By targeting tumor cells, nanoparticles can greatly reduce the minimal drug toxicity to healthy tissues/organs [153]. Due to its controllability and traceability, nanotechnology-based PDT [154,155] and thermotherapy [156] may be a powerful method for cancer research and treatment in the future. The early treatment of melanoma is effective, and diagnosis is necessary before metastasis occurs.…”
Section: Nanoparticle-based Strategies For Melanoma Photodynamic Thermentioning
confidence: 99%